By reducing production of vascular endothelial growth factor octreotide improves the peritoneal vascular alterations induced by hypertonic peritoneal dialysis solution - Günal, AI; Celiker, H; Akpolat, N; Üstündag, B; Duman, S; Akcicek, F (Multimed Inc, 2002)
Objective: Chronic peritoneal dialysis (PD) may eventually result in vascular alterations of varying degree, which lead to progressive reduction in dialytic efficacy. Although the pathogenesis has not been elucidated yet, vascular endothelial growth factor (VEGF) has been proposed to play a central role in the process leading to vascular alterations. Design: Rats were allocated to three groups: no treatment, intraperitoneal introduction of hypertonic PD solution alone, and intraperitoneal introduction of hypertonic PD solution plus octreotide. After 4 weeks, a 1-hour peritoneal equilibration test (PET) was performed. Dialysate-to-plasma urea ratio (D/P urea), glucose reabsorption (D-1/D-0 glucose), ultrafiltration volume (UF), and levels of dialysate protein and VEGF were determined. Peritoneal membrane histology was evaluated by light microscopy. Results: Compared with the control group, rats treated with hypertonic PD solution showed dramatically deranged peritoneal function tests (UF: 5.8 +/- 0.9 mL vs 1.3 +/- 0.6 mL; D/P urea: 0.49 +/- 0.1 vs 0.74 +/- 0.04; D-1/D-0 glucose: 0.55 +/- 0.05 vs 0.34 +/- 0.06) and morphology (thickness: 4.6 +/- 0.4 g vs 62 +/- 12 g; neovascularisation: 0.1 +/- 0.3 vessels per field vs 2.2 +/- 0.3 vessels per field). Similarly, a higher level of VEGF was found in the rats treated with hypertonic PD solution. In rats treated with hypertonic solution plus octreotide, peritoneal thickness was not completely reduced (25 +/- 5 g), but peritoneal functions were protected (UR 4.0 +/- 0.5 mL; D/P urea: 0.58 +/- 0.02; D-1/D-0 glucose: 0.51 +/- 0.02). Moreover, VEGF level and neoangiogenesis were significantly less in the octreotide group than in the group treated with hypertonic dextrose alone. Conclusion: Our data document that, by increasing the production of VEGF, a high glucose concentration can cause vascular alterations within the peritoneal membrane. Octreotide can protect against the vascular alterations and preserve peritoneal function by inhibiting overexpression of VEGF and regulating the inflammatory response in the peritoneum.
Keywords: glucose-based dialysis solutions; neoangiogenesis; vascular endothelial growth factor; octreotide